Synthesis and biological evaluation of 2-(arylethynyl)quinoline derivatives as mGluR5 antagonists for the treatment of neuropathic pain - Son, Myung-Hee; Kim, Ji Young; Lim, Eun Jeong; Baek, Du-Jong; Choi, Kihang; Lee, Jae Kyun; Pae, Ae Nim; Min, Sun-Joon; Cho, Yong Seo (Pergamon Press Ltd., 2013)
We described here the synthesis and biological evaluation of mGluR5 antagonists containing a quinoline ring structure. Using intracellular calcium mobilization assay (FDSS assay), we identified compound 5n, showing high inhibitory activity against mGluR5. In addition, it was found that compound 5n has excellent stability profile. Finally, this compound exhibited favorable analgesic effects in spinal nerve ligation model of neuropathic pain, which is comparable to gabapentin. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: METABOTROPIC GLUTAMATE RECEPTORS; RAT MODEL; 2-METHYL-6-(PHENYLETHYNYL)-PYRIDINE MPEP; ALLOSTERIC MODULATORS; POTENT; ALLODYNIA; COGNITION; DISEASE; ANXIETY